Latent profiles and transitions of social isolation among older adults and their influencing factors: a person-centered approach - Liu, Xuezhi; Zhang, Yanzhen; Wu, Jianxiao; Zeng, Yadi; Guo, Lingjing; Ye, Baojuan (Frontiers in Public Health, 2025)
IntroductionIn the context of global aging, it is crucial to understand the heterogeneity, changing trends, and influencing factors of social isolation in older people.Methods7198 older people over 60 in China Longitudinal Aging Social Survey in 2016 and 2018 were analyzed, using Latent Profile Analysis, Latent Transition Analysis, and multiple logistic regression analysis.ResultsThe study identified five categories of social isolation among older people; the rural, widowed, with low daily living activity ability, and with low cognitive ability were more likely to belong to the social isolation category; the stability of various profiles of social isolation was strong, but the high-level social network category had the danger of changing to the medium-level social network category and the social isolation risk category; over time, those with high daily living activity ability moved into worse social isolation categories, while those with high cognitive ability moved into better categories.DiscussionThe social isolation status of the older adult had group heterogeneity and transitioned over time. The findings provide empirical evidence for taking targeted measures based on the influencing factors in older people to achieve successful aging.